Exclusion of black women: an analysis of the film "Cruzed Stories" (Research, Society and Development, 2019)
In the social practice of exclusion, the factors race and gender are added when considering the historical disadvantages for black women. In the face of this double devaluation, black women are the most marginalized slice of society. Although the current scenario can be considered as a reduction of social inequalities, there are still unprivileged patterns for this social group of participation in education, labor market, health and other public spaces. This article analyzed the film "Cross Stories" in the context of the 60s, in order to identify processes of exclusion of black women, making comparisons with the current reality of blacks in Brazil. It was concluded that from the 60's there was little evolution regarding the rights of black women, being configured as maintenance of the exclusion and collective deprivation, refusal and abandonment of this social group in the country.